Infrastructure-less and calibration-free RFID-based localization algorithm for victim tracking in mass casualty incidents - Zhuorui Yang; Ganz, Aura (2016 IEEE Symposium on Technologies for Homeland Security (HST), 2016)
We introduce an active RFID-based algorithm for real-time tracking of victims during a Mass Casually Incident (MCI). By using responders locations obtained from GPS on their Smartphones as mobile anchors and active RFID readings from the victims, the proposed localization algorithm obtains average localization accuracy commensurate with GPS [1] (under 20 ft.). The proposed algorithm is a mobile, scalable, affordable, calibration-free and infrastructure-less solution, which makes it suitable for use in an MCI.